2008
DOI: 10.1111/j.1365-2761.2008.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonid fish viruses and cell interactions at early steps of the infective cycle

Abstract: A flow cytometric virus-binding assay that directly visualizes the binding and entry of infectious pancreatic necrosis virus (IPNV), infectious haematopoietic necrosis virus (IHNV) and virus haemorrhagic septicaemia virus (VHSV) to several cell lines was established. The highest efficiency of binding was shown by the BF-2 cell line and this was used to study, at the attachment level, the interactions of these cells with salmonid fish viruses in coinfections, and to further determine if the earliest stage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…Nevertheless, a more restricted distribution of IHNV in internal organs could be observed during the acute stage of the disease, and no virus was detected in the brain. The small reduction of the percentage of infection of both viruses between single and dual infections (96 versus 89% in average, respectively, for VHSV and 97 versus 73% in average, respectively, for IHNV) are comparable to the reduction of VHSV and IHNV binding on the cell surface as estimated with biotinylated viruses in single and double infections (91 versus 72% for VHSV and 91 versus 76% for IHNV, respectively) (17). These results suggest that the light interference observed between the two viruses could be explained by a competition for the same cell receptor as that demonstrated by Bearzotti et al, who identified the fibronectin as a major cell component allowing fish rhabdoviruses to bind to the target cells (3).…”
Section: Discussionmentioning
confidence: 57%
“…Nevertheless, a more restricted distribution of IHNV in internal organs could be observed during the acute stage of the disease, and no virus was detected in the brain. The small reduction of the percentage of infection of both viruses between single and dual infections (96 versus 89% in average, respectively, for VHSV and 97 versus 73% in average, respectively, for IHNV) are comparable to the reduction of VHSV and IHNV binding on the cell surface as estimated with biotinylated viruses in single and double infections (91 versus 72% for VHSV and 91 versus 76% for IHNV, respectively) (17). These results suggest that the light interference observed between the two viruses could be explained by a competition for the same cell receptor as that demonstrated by Bearzotti et al, who identified the fibronectin as a major cell component allowing fish rhabdoviruses to bind to the target cells (3).…”
Section: Discussionmentioning
confidence: 57%
“…In fact, several VNNV reassortant isolates have been obtained from cultured diseased Senegalese sole and gilt‐head seabream (Toffolo et al., ; Olveira et al., ). The coexistence of two different viruses in a single animal may affect the course of both viral infections, as has been previously described for several fish viruses (Chinchar et al., ; Johansen and Sommer, ; Pakingking et al., ; Byrne et al., ; de las Heras et al., ; Kuo et al., ). Regarding the nodavirus, Nishizawa et al.…”
Section: Introductionmentioning
confidence: 62%
“…(). This inhibition may be the consequence of the replication of the first virus, the competence for the same cellular receptors (de las Heras et al., ), the induction of an antiviral factor (Chinchar et al., ), or it may be caused by the stimulation of the host interferon (IFN)‐mediated immune system by the first‐inoculated virus (Johansen and Sommer, ; Byrne et al., ). However, the implication of the host IFN‐mediated immune system on the superinfective virus replication could not be tested in this work due to the lack of knowledge regarding the E‐11 immunogenic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The actual cause of the reduced pathogenesis is not known, but IPNV interferes with IHNV replication in cell cultures as well (Alonso et al 1999). Using green fluorescent protein labeled IHNV, VHSV and IPNV in flow cytometry experiments on BF-2 cells, de las Heras et al (2008) demonstrated a significant inhibition of IHNV uptake when coinfected with IPNV but no inhibition of VHSV uptake in IPNV coinfections. Using green fluorescent protein labeled IHNV, VHSV and IPNV in flow cytometry experiments on BF-2 cells, de las Heras et al (2008) demonstrated a significant inhibition of IHNV uptake when coinfected with IPNV but no inhibition of VHSV uptake in IPNV coinfections.…”
Section: Epizootiologymentioning
confidence: 99%
“…A study examining competition for receptors as possible cause of this inhibition was conducted by de las Heras et al (2008). Furthermore, in a coinfection one virus can suppress the replication of other viruses.…”
Section: Detectionmentioning
confidence: 99%